Making Freud more Freudian - Rothstein, Arnold, 1936- (Karnac, 2010)
This book demonstrates the clinical value of "making Freud more Freudian". The theoretical contributions of Charles Brenner are summarized and emphasized. They are built on an elaboration of Arlow's "fantasy function" and Freud's "compromise formation". The author applies this theoretical perspective in elaboration of the concepts of narcissism, masochism, shame and guilt to the distinction between psychiatric and psychoanalytic diagnoses, as well as to a variety of specific clinical topics. Finally, the author emphasizes that the ubiquity of unconscious conflict demonstrates that all percepti.